THU0013 Longterm Outcomes of Children Born to Mothers with SLE Exposed to Azathioprine in Pregnancy. (10th June 2014) - Gayed, M.; Khamashta, M.; Dimitrov, B.D.; Leone, F.; Veronica, T.; Bruce, I.; Giles, I.; Teh, L.-S.; McHugh, N.; Akil, M.; Edwards, C.; Gordon, C.
Abstract : Background: Azathiopine (AZA) is commonly used to ensure SLE disease control during pregnancy. There is little information regarding long term outcomes of these children. Objectives: We aimed to assess if AZA exposure during pregnancy and lactation was associated with adverse outcomes for children born to mothers with lupus. Methods: Women attending lupus clinics, with available pregnancy data, were consented to take part. A standard questionnaire developed for a multi-centre study was used to collect the data. Results: Complete data was available for 287 children born alive to 200 women: 66% Caucasian, 15% South Asian, 10% Afro-Caribbean, 1% Chinese, 1% Hispanic, 4% other and 4% not stated. The median (range) age of women at delivery was 32 (19-44) yrs, and duration of disease was 6 (0.5-27) yrs. Two groups were studied: 89 children exposed to AZA during pregnancy &/or breast-feeding (group A) vs 198 children unexposed (group NA). Maternal renal disease (group A 38/67, 57% vs group NA 28/175, 16%), use of maternal prednisolone (group A 78/89, 87% vs group NA 93/198, 47%) and aspirin (group A 70/84, 83% vs group NA 132/200, 66%) were significantly increased in group A compared with group NA (p<0.005). No significant differences in exposure to hydroxychloroquine or heparin between the groups was identified. There was no significant difference in maternal pre-eclampsiaa, hypertension, anti Ro and/or anti-La antibodies, between the two groups. The presence of maternal lupus anticoagulant and/or anticardiolipin antibodies (ACA) was statistically higher in group A 44/73 (60%) vs group NA 79/178 (49%), p=0.03. However the presence of the antibodies individually was not different. Median age of children at enrolment in group A was 3.2, (range 0-17.1) vs group NA 3.1 (0-16.2) years. The median birth weight in group A was 2.8 (0.6-4.4)kg vs 3.1 (0.7-4.7) kg in group NA and gestational age in group A was 36.3 (27-42) wks vs 38 (25-42) wks in NA. These were both statistically significant. Using univariate analysis children exposed to AZA had a significantly increased rate of hospital admissions for infection (group A 25/89, 28% vs group NA 28/198, 14%, p=0.005), but not for overall hospital admissions (group A 29/84, 35% vs group NA 45/192, 23%, p=0.07) or out- patient visits. When the effect of AZA was adjusted by multifactor logistic regression for maternal renal disease and prednisolone use, the relationship became non-significant (OR 1.73 (0.85-3.5), p=0.13, however, due to the lower sample size its power was <80%. Conclusions: This study shows that women with SLE who take AZA during pregnancy are more likely to have had renal disease, ACA and/or lupus anticoagulant and to use prednisolone. The median birthweight and duration of pregnancy was lower. There appeared to be an increased risk of hospital admission due to infection in the children of group A mothers. However, after adjusting for markers of maternal lupus disease severity this relationship disappeared. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1616